EFFECT OF SUB-CLINICAL HYPOTHYROIDISM ON CHOLESTEROL AND TRIGLYCERIDES - Aftab, Rana Khurram; Zubair, Syed Muhammad; Ijaz, Farhat; Aftab, Rana Rakhshan (Pakistan Journal of Physiology, 2018)
Background: Sub-clinical Hypothyroidism (SCH) is associated with dyslipidemias which may increase the cardiovascular risk. The objective of this study was to compare the serum levels of cholesterol and triglycerides in subclinical hypothyroidism and normal euthyroid subjects. Methods: This cross-sectional comparative study had control group of 50 euthyroid subjects selected from Mayo Hospital, Lahore who were advised to get thyroid profile checked. Fifty sub-clinical hypothyroid patients were included on the basis of their thyroid profile reports. Fasting blood samples were taken from both the groups for analysis of serum levels of T4, total cholesterol and Triglycerides. Studentâ€™s t-test was used to compare the mean values, and pâ‰¤0.05 was considered statistically significant. Results: Mean Triglyceride level in SCH was 168.28 mg/dl, and in euthyroid controls it was 133.62 mg/dL (p<0.001). There were no differences of total cholesterol in both groups with value of 190 mg/dL in SCH group and 189.12 in control group (p=0.912). Triglycerides level was raised in SCH and there was no pronounced effect on total cholesterol. Conclusion: The effects of SCH are more pronounced on triglycerides and less on total cholesterol.